INTERNATIONAL ASSESSMENT OF THE DEVELOPMENT OF UKRAINE'S TRANSPORT SECTOR - Bilik, Volodymyr (SWorldJournal, 2025)
This article presents an analysis of the development of Ukraine's transport sector in an international context. Key transport performance indicators are assessed and compared with those of EU member states and neighboring countries. The study identifies t